Global Innovations in City Gardening for Food and Nutritional Security - R. Vasantha, (Journal of Agricultural Extension Management, 2023)
Today, the importance of both rural and urban areas in reconstructing food systems is growing. It is necessary to revisit how our food is grown, distributed and eventually ends up on our plates. From a production perspective, agro ecological practices and family farming must be viewed as a way of life whereas availability of safe, nourishing and culturally appropriate food for everyone is vital from a consumption standpoint. Urban and periurban gardening will make cities sustainable and resilient which is the prime focus of the UN’s Sustainable Development Goal 11. With an acknowledged status and duty legally required by the COAG, 1999 FAO worked proactively through its multidisciplinary initiative “Food for the Cities.” (Makiko Taguchi and Guido Santini, 2019). Innovations in City and Peri-urban gardens in different parts of world are ample. Urban farming contributes 30%, 50% and 85% of the vegetables consumed in Kathmandu, Karachi, and Shanghai respectively (FAO, 1996). The strategy for assisting the regional food system through creative vertical facades for seed gathering, green walls and floating greenhouses fits Shanghai’s strategy adequately. Many innovations in marketing of urban farming produce such as organizing farm visits, monthly ‘healthy lunches’ and guaranteed purchase of vegetables before harvest are seen in the city of Rosario, Buenos Aires